2022
DOI: 10.1182/blood.2021014520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnostic genetics on remission MRD and transplantation outcomes in older patients with AML

Abstract: Older patients with acute myeloid leukemia (AML) have high relapse risk and poor survival after allogeneic hematopoietic cell transplantation (HCT). Younger patients may receive myeloablative conditioning to mitigate relapse risk associated with high-risk genetics or measurable residual disease (MRD), but older adults typically receive reduced-intensity conditioning (RIC) to limit toxicity. To identify factors that drive HCT outcomes in older patients, we performed targeted mutational analysis (VAF≥2%) on diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 56 publications
0
26
1
Order By: Relevance
“…In addition, serial MRD measurements can be used to monitor treatment response while on therapy and potentially serve as surrogate endpoints. However, pitfalls of overutilizing MRD presently include heterogeneity of mutations, some of which do not represent leukemia driving mutations, and the fact that certain MRD measures have not been definitively proven to imply imminent relapse ( 60 ). Maintenance therapy trials that prospectively plan to follow MRD status between intervention and control arms will be invaluable to determine the clinical utility of MRD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serial MRD measurements can be used to monitor treatment response while on therapy and potentially serve as surrogate endpoints. However, pitfalls of overutilizing MRD presently include heterogeneity of mutations, some of which do not represent leukemia driving mutations, and the fact that certain MRD measures have not been definitively proven to imply imminent relapse ( 60 ). Maintenance therapy trials that prospectively plan to follow MRD status between intervention and control arms will be invaluable to determine the clinical utility of MRD.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-transplant MRD negativity by MFC, PCR, or NGS has also been shown to be predictive of superior post-transplant outcomes including improved OS, improved leukemia free survival (LFS), and reduced incidence of relapse in patients of all ages ( 22 , 23 ). However, findings from recent studies have also suggested that pre-transplant MRD status by flow or NGS may not be independently predictive of post-transplant LFS or OS in patients older than 60, particularly in patients who are treated with lower intensity therapy for remission induction ( 24 , 25 ). The impact of treatment intensity on achievement of MRD negativity in this patient population will be an important question for future studies to address, as will the impact of MRD negativity on post-transplant outcomes for patients treated with intensive vs. targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…73 Molecular characteristics at diagnosis in patients 60 years or older with AML who undergo allo-HCT in CR1 are predictive of leukemia-free survival and persistence of MRD. 74 These data should, therefore, be integrated into the transplant decision.…”
Section: Transplant Consideration/maintenance Therapies In First Remi...mentioning
confidence: 99%